The Resilience Paradox: A Climate Change Coping Mechanism in the Farm Households from Samarkand Region of Uzbekistan - Bekhzod Egamberdiev; Abdulla Primov; Sherzod Babakholov (ZBW - Leibniz Information Centre for Economics, 2025)
The climate change literature broadly characterizes resilience as the capacity of the household to withstand the negative consequences of climate change. However, most studies on climate change resilience use a general or inconclusive relationship between resilience and the coping strategy of the household. To extend the existing literature, we applied FAO's Resilience Index Measurement Analysis (RIMA) approach to construct the Resilience Capacity Index (RCI). Using Latent Class Analysis (LCA), we cluster homogenous classes describing household coping strategy behavior. With an Instrumental Approach (IA), we explore how climate change resilience changes the perception of coping strategies. Our findings generally conclude that there is a negative relationship between long-term RCI and short-term household coping strategies. This relationship is particularly significant for changing planting dates, planting short-cycle crop varieties, crop diversification, and tree planting. We can conclude that climate change resilience may diminish the motivation to activate short-term coping strategies for policy interventions.
Keywords: O13; O20; Q12; 330; Climate change; Resilience; Household Capacity; Agriculture; Latent Class Analysis (LCA)